MELACAK NILAI-NILAI PENDIDIKAN KARAKTER DALAM FILM ANIMASI NUSSA DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Ningsih, Yuni Prastiwi; Afwadzi, Benny (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
With the sophistication of technology, the process of inculcating character education values nowadays can be done by utilizing the movie as a media. The existence of this media will help the process of inculcating character education values in the society, especially for children and teenagers who often enjoy it. One of the most popular animation movies today is an animation movie created by Indonesia with a title “Nussa” which is shown on YouTube. The animation movie of Nussa contain many characters education values that are relevant to Islamic Education. Acording to the background, this research article focuses to determine: (1) character education values in animation movie of Nussa, and (2) the relevance of character education values in animation movie of Nussa to Islamic Education values. This research uses a qualitative approach and it is a library research type. This research focuses on 5 episodes in animation movie of Nussa which is found in the second season. The data was collected through documentation technique and it was analyzed through content analysis technique, namely analyzing the contents of the dialogue among the characters, settings, and events contained in the movie. By using content analysis to analize the film, The authors come to the conclusion (1) there are 10 values of character education in animation movie of Nussa, namely religious value, honest value, tolerance value, creative value, curiosity value, appreciate achievement value, friendly/communicative value, environmental care value, social care value, and responsibility value. (2) Character education values in animation movie of Nussa have relevance to Islamic Education values. Religious value is relevant to faith value. Religious value, honest value, tolerance value, and social care value are relevant to sharia value. Religious value, honest value, tolerance value, creative value, curiosity value, appreciate achievement value, friendly/communicative value, environmental care value, social care value, and responsibility value are relevant to moral value. Abstrak Dengan kecanggihan teknologi, proses penanaman nilai-nilai pendidikan karakter dapat dilakukan dengan memanfaatkan media film. Keberadaan media film akan membantu proses penanaman nilai-nilai pendidikan karakter di masyarakat, khususnya pada anak- anak dan remaja yang gemar menonton film. Salah satu film animasi yang digemari adalah film animasi buatan Indonesia yang berjudul “Nussa” yang ditayangkan di YouTube. Film animasi Nussa memuat nilai-nilai pendidikan karakter yang relevan dengan pendidikan Islam. Berdasarkan hal tersebut, artikel penelitian ini fokus untuk meneliti (1) nilai-nilai pendidikan karakter yang terdapat dalam film animasi Nussa, dan (2) relevansiny dengan nilai-nilai Pendidikan Agama Islam. Penelitian ini menggunakan pendekatan kualitatif dan termasuk dalam jenis penelitian kepustakaan (library research). Penelitian ini berfokus pada 5 episode dalam film animasi Nussa yang terdapat pada musim kedua. Dengan menggunakan analisis isi (content analysis) untuk menganalisis film ini, penulis menyimpulkan (1) terdapat 10 nilai pendidikan karakter dalam film animasi Nussa, yaitu nilai religius, nilai jujur, nilai toleransi, nilai kreatif, nilai rasa ingin tahu, nilai menghargai prestasi, nilai bersahabat/komunikatif, nilai peduli lingkungan, nilai peduli sosial, dan nilai tanggung jawab. (2) Nilai-nilai pendidikan karakter dalam film animasi Nussa memiliki relevansi dengan nilai-nilai Pendidikan Agama Islam. Nilai karakter religius relevan dengan nilai akidah. Nilai karakter religius, jujur, toleransi, dan peduli sosial relevan dengan nilai syariat. Nilai karakter religius, jujur, toleransi, kreatif, rasa ingin tahu, menghargai prestasi, bersahabat/komunikatif, peduli lingkungan, peduli sosial, dan tanggung jawab relevan dengan nilai akhlak.